Do Parents of Sick Children Use Religious Coping in Argentina? - ÇAKSEN, HÜSEYIN (Pakistan Journal of Medical & Health Sciences, 2024)
Coping is the use of cognitive and behavioral strategies to manage the demands of a situation when these are appraised as taxing or exceeding one’s resources or to reduce the negative emotions and conflict caused by stress1. Religion is a declaration, a manifesto, describing both the One who made this beautiful universe and the universe itself2. Religious coping is a means of seeking Allah’s help, trusting and taking refuge in Allah, finding solace in religious provisions/teachings, and praying/worshiping more than usual during stressful events of life such as illness, calamity, death, or circumstances where a person is helpless3. Herein, we briefly discussed the use of religious coping among parents who had children with chronic disease to attract attention to the importance of religion coping.